Diversity, antimicrobial production, and seasonal variation of honey bee microbiota isolated from the honey stomachs of the domestic honey bee, Apis mellifera - Mundo, Melissa A.; Xiong, Zirui Ray; Galasong, Yupawadee; Manns, David C.; Seeley, Thomas D.; Vegdahl, Ann Charles; Worobo, Randy W. (Frontiers in Sustainable Food Systems, 2023)
The antimicrobial nature of honey and its related apiological origins typically focus on basic chemical analysis without attempting to understand the diversity of the microbial component. The antibacterial activity, chemical characterization and diversity of bacteria isolated from Apis mellifera honey stomachs and hive honey collected throughout the honey production season is presented. After screening > 2000 isolates, fifty were selected and characterized by 16S rRNA gene homology, Gram stain, catalase and protease tests, as well as for antibacterial activity against select indicators. Antibacterial producing isolates were predominantly from the Pseudomonas, Paenibacillus, Lonsdalea, Serratia, and Bacillus genera. Isolates collected from honey stomachs in April displayed the highest level of activity (27%). While April isolates did not demonstrate activity against the Gram-negative bacteria tested, 59% of July, 33% of September and 100% of the honey isolates did. The predominant honey stomach isolates were Pseudomonas spp. (April), P. polymyxa (July, Sept.), Lonsdalea iberica (Sept.). Chemical characterizations of the antimicrobial compounds show most to be antibiotic in nature with the minority being potential bacteriocins. This study offers a first glimpse into the variability and diversity of the bacteria/host interactions found within the honey stomach of the domestic honey bee while revealing a novel source of potentially beneficial antimicrobial compounds.